The Application of Multi-Dimensional Radar Mapping Model (MDRM-Model) on the People’s Republic of China (PRC) and the U.S. Economy - Ruiz Estrada, Mario Arturo (WILAYAH: The International Journal of East Asian Studies, 2015)
This paper proposes a new multidimensional graphical model to monitoring the GDP growth rates in real prices behavior and the GDP formation accumulation from any country in the short and long run through the uses of “the Multi-Dimensional Radar Mapping Model (MDRM- Model).” Hence, the MDRM-Model is based on the plotting of different coordinates that represents a large number of GDP growth rates in real prices on the top of a large number of perimeters. Each perimeter represents different periods of time in our analysis. In our case, we are using the Multi-Dimensional Radar Mapping coordinate system (MDRM-Coordinate System) to build the MDRM-Model respectively. Moreover, the MDRM-Model can facilitate the visualization of different GDP growth rates in real prices simultaneously in different periods of time (years) or spaces (countries) that follows a logical order into the same graphical space. The MDRM-Model was applied on the economies of People’s Republic of China (PRC) and U.S. to analyze the process of GDP formation accumulation in the last past forty years in both economies.